Obraz světa a člověka v uměních starověku - Bouzek, Jan (Lidé města, 2006)
The article discusses how the picture of man and his world changed from the Neolithic until the end of Classical antiquity. The two ways of perception, through the eye and through the ideas about what I see, are present since the beginnings of visual arts, but its development underwent important changes. The art of the Late Paleolithic and Mesolithic reflects the early mind of “dreaming”, those of the Maltese and Cycladic figurines, though based on Geometric construction, reflects still similar kind of perception based on inner experience. Late Neolithic and Early Bronze Age in the Mediterranean representations rather depict what is arising (das Werdende) than what already exists (das Seiende). When the pictures became more realistic, still the composition derives from continuous rhythmic patters, as spiral or wave line. The observer is not separate from the picture, it is feeling to be inside the space of the picture, while the perspective is composed from viewing the objects from several angles; the final representation combines several views, and the objects represented are not governed by the observer’s position. The world of art - since the Sumerian times - had to reflect the entirety of the sensual world - besides the human and divine (i.e. idealised human) worlds the animals, plants and minerals are represented to produce a reflection of the whole macrocosmos in the microcosmos of art in order to harmonize the relations between man and the gods, the entirety of the world and the human being. The emancipation from the traditional sapiential wisdom based on memory and transmitting already fixed experience was replaced in the Early Iron Age by philosophy, by attempts of intellectual explaining of the reality: this is also reflected by the progress of visual arts in Greece, trying to understand human body and the soul behind it appearance. The Etruscan mind was more traditional, preferring - against the Romans - the teleological explanation to causal; it this it was near to the mind of the Celts. The Romans became more conscious of the individuality; Roman portraits are more individual than those of the Greeks, thus showing the progress of emancipation of the individual from the group identity. Late Antiquity preferred the new approach in idealization of the reality; the portrait was changed into icon, the optic perception of light prevailed over the physical forms, like in the Ravenna mosaic or in the jewellery using colour stones; it was believed that precious stones enable the contact between the human world and those of the angels.